Mental health priorities in Vietnam: a mixed-methods analysis - Niemi Maria; Thanh Huong T; Tuan Tran; Falkenberg Torkel (BMC, 2010)
Abstract Background The Mental Health Country Profile is a tool that was generated by the International Mental Health Policy and Services Project to inform policy makers, professionals and other key stakeholders about important issues which need to be considered in mental health policy development. The Mental Health Country Profile contains four domains, which include the mental health context, resources, provision and outcomes. We have aimed to generate a Mental Health Country Profile for Vietnam, in order to highlight the strengths and weaknesses of the Vietnamese mental health situation, in order to inform future reform efforts and decision-making. Methods This study used snowball sampling to identify informants for generating a Mental Health Country Profile for Vietnam, and the data gathering was done through semi-structured interviews and collection of relevant reports and documents. The material from the interviews and documents was analysed according to qualitative content analysis. Results Marked strengths of the Vietnam mental health system are the aims to move toward community management and detection of mental illness, and the active involvement of several multilateral organizations and NGOs. However, there are a number of shortages still found, including the lack of treatment interventions apart from medications, the high proportion of treatments to be paid out-of-pocket, prominence of large tertiary psychiatric hospitals, and a lack of preventative measures or mental health information to the public. Conclusions At the end of this decade, mental health care in Vietnam is still characterised by unclear policy and poor critical mass especially within the governmental sector. This initial attempt to map the mental health situation of Vietnam suffers from a number of limitations and should be seen as a first step towards a comprehensive profile.